Masculinities, Social Change, and Development - Greene, Margaret E. (Washington, DC: World Bank, 2012)
There is increasing awareness of the costs that gender inequality imposes on individuals and societies, and the resulting implications for development prospects. Gender disparities, many of which begin at childhood, have significant adverse long-term effects on both individuals and societies. Many longstanding differences in gender roles and expectations, while based on institutions and norms that may have been functional in the past, need to be modified if development progress is to be accelerated in a time of rapid technological and social change. Evidence from around the world suggests that societies that promote more equal opportunities for men and women also have higher growth, lower poverty, and better development outcomes.